2009
DOI: 10.17221/3088-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Selenium metabolism in goats - maternal transfer of selenium to newborn kids

Abstract: AbStrAct:The aim of our study was to compare the concentration of selenium (Se) and the activity of glutathione peroxidase (GSH-Px) in the whole blood of goats and their newborn kids. The experiment involved 25 gravid, clinically healthy goats of the white shorthaired breed. On the day of delivery, we took whole blood from the mother and her newborn kid before the kid drank the first colostrum. In mothers, the measured average concentration of Se in whole blood was 149.60 ± 45.01 μg/l, the average concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
15
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 18 publications
2
15
0
Order By: Relevance
“…Ludvikova et al (2005) defined for the practical establishment of selenium deficiency in horses the marginal level of glutathione peroxidase activity as 200-300 μkat/l in whole blood when the deficiency level for selenium is set as 75-100 μg/l of Se in the blood. Misurova et al (2009a) found that a selenium concentration of 100 μg/l corresponds with a glutathione peroxidase activity 700 μkat/l in the blood of adult goats and 720 μkat/l in the blood of newborn kids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ludvikova et al (2005) defined for the practical establishment of selenium deficiency in horses the marginal level of glutathione peroxidase activity as 200-300 μkat/l in whole blood when the deficiency level for selenium is set as 75-100 μg/l of Se in the blood. Misurova et al (2009a) found that a selenium concentration of 100 μg/l corresponds with a glutathione peroxidase activity 700 μkat/l in the blood of adult goats and 720 μkat/l in the blood of newborn kids.…”
Section: Discussionmentioning
confidence: 99%
“…In the Czech Republic, for example, this has been demonstrated by Pavlata et al (2000) in cattle, Pavlata et al (2005) and Misurova et al (2009a) in goats and Ludvikova et al (2005) in horses. In the Czech Republic a correlation between concentration of selenium and activity of glutathione peroxidase in whole blood has not been described for sheep.…”
mentioning
confidence: 96%
“…Primarily Se, together with other elements such as Zn or Cu, is known for its activity against reactive oxygen forms in tissues. Additionally, Co, Cu, Fe, Se and Zn deficiencies reduce resistance to infection and increase susceptibility to infectious maladies (Spears 2000;Bhaskaram 2002;Misurova et al 2009). Biological availability and absorption of minerals also differ between ruminants and nonruminants (Spears 2003), and between ruminants, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, other indirect diagnostic methods can be used, such as for example an identification of the activity of an enzyme dependent on the particular microelement, such as glutathione peroxidase in the case of Se (Pavlata et al, 2000;Ludvikova et al, 2005;Misurova et al, 2009b). Milk and hair are other materials used for diagnostics (Gabryszuk et al, 2008).…”
mentioning
confidence: 99%